Going online and taking the plane. From San Francisco to Jerusalem: the physical and electronic networks of “Jewish Mindfulness” - Niculescu, Mira (Online - Heidelberg journal of religions on the internet, 2015)
In this article, I analyze the emergence of a new hybrid practice within American Judaism: “Jewish mindfulness”. Jewish mindfulness is a new meditation practice inspired from “mindfulness meditation”, a westernized form of Buddhist meditation. I look at the role played in the Internet in the rapid success and in the geographical unfolding of this new practice within the transnational English speaking Jewish religious networks. First, I retrace the emergence of the practice of Jewish mindfulness and the role played by Internet in this process. Second, I focus on the genealogical and geographical structure of today’s Jewish mindfulness networks. Finally, through focusing comparatively on two groups offering the practice of “Jewish mindfulness”, I show how the Internet becomes the surface of expression of hybrid discourses that are not necessarily expressed as such. In conclusion I suggest that electronic networks can be used to support, rather than to replace “offline” religious connections.